Benefits of controlled-release fertilizers for potato sustainable nitrogen management - Xue, Huiling; Zheng, Xiaofan; Wei, Hong; Yang, Jing; Alva, Ashok; Fan, Mingshou; Zhang, Ziyi (Frontiers in Environmental Science, 2024)
Evaluation of potato response to controlled-release fertilizer (CRF), as sole source of nitrogen (N) or as blend with soluble N source, is essential to: (i) develop best management recommendations for using CRF in potato production; and (ii) provide guidelines to CRF manufacturers for developing an optimal product. This study was aimed to evaluate the potato yield and quality responses to N CRF (polymer coated urea; PCU) vs. soluble N sources. The experiments were conducted in major potato growing regions in the USA and China. The current industry recommended practice of 112 kg N/ha pre-plant soil broadcast of urea plus 5 in-season fertigations of 224 kg N/ha as urea ammonium nitrate (UAN-32) was compared to single pre-plant application of 224 kg N/ha as CRF as sole source of N or as multiple blends of CRF and soluble N source (i.e. Urea) at various ratios. Results demonstrated that petiole nitrate_N (NO3_N) levels and tuber yield with single pre-plant broadcast application of 224 kg N/ha as CRF/Urea blends (25/75 or 50/50 ratio) were similar to those with industry standard N management practice. N uptake and yield were significantly greater with 220 kg/ha N as CRF as compared to those with the same N rate as urea. Unlike the current potato industry N practice, using CRF as either sole source of N or blended with urea enables reduced total N rate and application frequency.